Effect of Short-Course Oral Ciprofloxacin on Isoflavone Pharmacokinetics following Soy Milk Ingestion in Healthy Postmenopausal Women - Nathathai Temyingyong (2019)
© 2019 Nathathai Temyingyong et al. Soy isoflavones have several potential benefits related to postmenopausal health. Isoflavone glycosides, found predominantly in nonfermented soy products, e.g., soy milk, require conversion by gut microbiota to their respective bioavailable aglycones prior to absorption into portal circulation. Use of short-course oral ciprofloxacin for the treatment of acute uncomplicated cystitis, the incidence of which is increasing among postmenopausal women, might adversely affect gut microbiota. The objective of this one-group pre-post treatment study was to determine the effect of short-course oral ciprofloxacin on isoflavone pharmacokinetics in healthy postmenopausal women. Eleven postmenopausal subjects were assigned to consume a single oral dose of 375 mL UHT soy milk (SOY phase). Blood samples were collected immediately before soy milk ingestion and at specific times for 32 hours after soy milk ingestion. Following a washout period of at least seven days, subjects were assigned to take 250 mg oral ciprofloxacin after breakfast and dinner for three days, followed by a single oral dose of 375 mL UHT soy milk the next day (CIPRO/SOY phase). Blood samples were collected at the same time points as in the SOY phase. Plasma samples were treated with β-glucuronidase/sulfatase and plasma concentrations of aglycones (genistein and daidzein) were determined using high-performance liquid chromatography. Cmax, AUC0-t, and AUC0-∞ of both aglycones and Tmax of genistein obtained from the CIPRO/SOY phase were significantly lower than those obtained from the SOY phase, while Tmax of daidzein and t 1/2 of both aglycones in the two phases were not significantly different.